Hearing assessment in a rare case of Hajdu Cheney syndrome - ., Priyanka; ., Shiffali; Singh, Manpreet; Singh, Jagdeepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Hajdu Cheney syndrome is extremely rare autosomal dominant congenital disorder of connective tissue. It may occur due to spontaneous de novo mutation and mutation in NOTCH-2 gene identified recently. Most characteristic features include aero-osteolysis involving phalanges of both hands and feet, osteoporosis, deformities of skull, mandible, spine and other bones, kyphoscoliosis and bone fractures. Rarely in some affected individuals, it causes joint hypermobility, dental problems, hearing loss, heart defects, kidney abnormality like polycystic kidneys, excess body hair and recurrent infections in childhood. It affects many parts of body particularly bones. Treatment is symptomatic. In this case report, we present a case of 14 years male child with features of Hajdu Cheney syndrome with genetic predisposition. Patient presented to ENT clinic with complaint of hearing loss.